Interior of Our Lady of the Rosary church - Mumbai Archive Project Team (Jio Institute, 2024)
The old Our Lady of the Rosary church was relatively smaller and could not accommodate the growing number of parishioners. Consequently, a new church was constructed over the course of two years, from 1924 to 1925, with numerous modifications made to the structure. The dimensions and height of the church were expanded to accommodate larger congregations. On February 14, 1926, the Bishop of Mysore consecrated the new church.